2023
DOI: 10.31557/apjcp.2023.24.2.551
|View full text |Cite
|
Sign up to set email alerts
|

Atractylodin and β-eudesmol from Atractylodes lancea (Thunb.) DC. Inhibit Cholangiocarcinoma Cell Proliferation by Downregulating the Notch Signaling Pathway

Abstract: Objective: Notch signaling pathway has been reported to be involved in the development and progression of various types of cancer, including cholangiocarcinoma (CCA). Compounds that modulate this signaling pathway could be promising candidates for CCA treatment and control. The study investigated the antiproliferative activities and modulatory effects of atractylodin and β-eudesmol, the two bioactive compounds of Atractylodes lancea (Thunb.) DC. , on Notch signaling and upstream molecules (Notch1 and Notch2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…To further investigate the efficacy of liensinine in treatment of ICC, we tried to combine liensinine with gemcitabine. Based on existing studies, 43–45 we set the concentration of gemcitabine on RBE and Hucc‐T1 to 10μM. Through colony formation test, wound healing assays, migration and invasion Transwell experiments, we found that, in RBE and Hucc‐T1 cells, liensinine combined with gemcitabine had certain curative effects on the proliferation, as well as on migration and invasion (Figures ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the efficacy of liensinine in treatment of ICC, we tried to combine liensinine with gemcitabine. Based on existing studies, 43–45 we set the concentration of gemcitabine on RBE and Hucc‐T1 to 10μM. Through colony formation test, wound healing assays, migration and invasion Transwell experiments, we found that, in RBE and Hucc‐T1 cells, liensinine combined with gemcitabine had certain curative effects on the proliferation, as well as on migration and invasion (Figures ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on existing studies, [43][44][45] tumor resistance to gemcitabine, [46][47][48][49] and therapy targeting on HIF-1a may improve the efficacy of gemcitabine. 50,51 Besides, available data does not rule out the possibility that gemcitabine directly or indirectly acts on HIF-1a.…”
Section: Liensinine Reversed the Emt Phenotype Of Icc Cells With High...mentioning
confidence: 99%
“…In addition, atractylon regulates the expression of thymopoietin antisense transcript 1 (TMPO-AS1) and coiled-coil domain-containing 183 antisense RNA 1 (CCDC183-AS1) and inhibits the invasion and migration of liver cancer cells [ 81 ]. β -eudesmol was found to have moderate activity against human cholangiocarcinoma (HuCCT-1) cell growth with an IC 50 (concentration that inhibits cell growth by 50%) value of 16.80 ± 4.41 µg/mL through the Notch signaling pathway and its upstream/downstream molecules in the CCA cell line at the gene and protein expression levels [ 82 ]. Moreover, β -eudesmol treatment (2.5–5 mg/kg) significantly inhibited the growth of H 22 and S 180 mouse tumor in vivo, which indicated that it inhibited angiogenesis via suppressing CREB activation in growth factor signaling pathway [ 83 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Eudesm-4(15)-ene-7α,11-diol (72), (5R,10S)-eudesm-4(15),7-diene-11-ol-9-one (73), and eudesm-4(15),7(11)-diene-9α,11-diol (74) were separated from A. lancea via silica gel column chromatography and preparative TLC [58]. Two new nitrogen-containing sesquiterpenoids, atractylenolactam A (75) and atractylenolactam B (76); two new sesquiterpene lactones, 8-methoxy-AT-V (77) and 15-acetoxyl AT-III (86); and four known analogs (78)(79)(80)(81)(82) were separated from A. macrocephala using column chromatography and preparative HPLC, and the absolute configurations were established using time-dependent density functional theory ECD (TDDFT-ECD) calculations [59,60]. Zhou et al [61] isolated six eudesmane-type sesquiterpenoids (83)(84)(85)(86)(87)(88) from A. lancea with repeated silica gel column chromatography, and their structures were determined using physiochemical and spectroscopic evidence.…”
Section: Eudesmane-type Sesquiterpenesmentioning
confidence: 99%